An Examination of Spatial Inequalities in Access to WASH Services in Pakistan - Liaqat, Aqsa; Ilyas, Muhammad; Ahmad, Ashfaq (Annals of Human and Social Sciences, 2024)
The availability of water is one of the most fundamental and essential needs of any economy. However, the unequal distribution of nature’s gifts, such as water, has become one of the major problems that developing countries like Pakistan are facing today. The unequal distribution and access to WASH (water, sanitation, and hygiene) must be addressed in order to minimize poverty in the country. UNICEF and WHO have developed a joint monitoring program to reduce inequalities and remove poverty all over the world. There are several goals in this Programed including goals 6.1 and 6.2 (equal distribution of WASH services). This study determines whether there is a spatial inequality in access to WASH services in Pakistan or not. The inequalities are studied between the regions of Pakistan as well as among the provinces. The study used cross-sectional data (2019 to 2020) from the PSLM survey. The sample size used in the study is 49, 510. One-way ANOVA and t-test techniques are used to analyze inequalities in this study. The results of the study indicate that there are significant inequalities in access to WASH services across provinces in Pakistan. The urban household has more equal access to WASH services than the rural areas. This study provides comprehensive information to policymakers for policy making. Encourage partnerships and collaboration among government agencies, civil society organizations, private sector entities, and communities in order to harness resources and knowledge. Engage the media, community leaders, and powerful figures to champion the cause and foster a gender-equal culture of access to WASH services.